The Academic Library of the Future - Boakye, Gifty (Ghana Library Journal, 2012)
An academic library is a library situated in an institution of higher learning, usually a university. college or polytechnic with the basic aim of providing needed information to enable the institution achieve its mission. An academic library by nature serves as a means to achieve an end and is not an end in itself. This presupposes that the academic library must be dynamic enough to respond to the changing needs of the institution that it serves. Changes in the education and information landscape in recent times and the emergence and adoption of Information Technology (IT) sometimes referred to as Information Communication Technology (ICT) has revolutionised the face of education as well as the production, presentation and dissemination of information. Technology has made it possible for institutions of higher learning to offer distance education programmes. where students are scattered all over the country and sometimes over the world. Changes in technology have also modified the information - seeking behaviours of most students andfaculty of universities and polytechnics. It is expedient therefore for the academic libraries to also adopt the use of ICT to enable them respond positively to theneeds of the constituency they serve and to remain relevant in the modern technological landscape. The paper defines ICT. looks at its benefits and challenges to the academic library and suggests ways of overcoming the challenges.